A Multi-Technique Approach to The Study of Hydantoins: From Isolated Molecules to Polymorphs - ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
Hydantoins have remarkable interest from the chemical and biological perspectives, and they have also been shown to receive widespread applications in medicine, agriculture and chemical industry. They have been clinically used as antiepileptic and antibacterial drugsand for cancer and AIDS treatments, and are also used currently as herbicides and fungicides. In this talk, 1 will present recent data on a series of simple hydantoins, obtained using a multi-technique approach that allowed characterizing the single molecules of these compounds in relation to their structure, vibrational spectra and photochemistry, and also to determine the spectroscopic and thermal properties oftheir neat condensed phases (with emphasis given to polymorphism). The main technique used for the investigation of the isolated molecules was matrix isolation infrared spectroscopy, complemented by up-to-date quantum chemical calculations. For the investigation of the condensed phases, differential scanning calorimetry (DSC), polarized-light thermomicroscopy, X-ray diffraction, and infrared and Raman spectroscopies were used. The used multidisciplinary methodology allowed to attain a considerably broad understanding of the structural, vibrational, photochemical and thermal properties of the hydantoin moiety, which may be seen as a gateway for assessing the reactivity and biological activity of this type of compounds.